The Vocabulary of the Septuagint and Literary Criticism: The Case of Numbers 27,15-23 - Kislev, Itamar (Biblica, 2009)
A careful attention to the change in the employment of Greek equivalents in the translation of Hebrew words in the Septuagint may help us to identify involvement of different translators. Such a change may sometimes point to some stages in the composition of the Hebrew text. In this article some interesting differences in the vocabulary of the Septuagint in the passage of the investiture of Joshua in Num 27, 15-23 are examined and with some other literal-critical considerations lead to exact exploring of the literal process of the graduated formation of the Hebrew passage.